Energy measurement system of a large-aperture high power laser experiment platform. (14th February 2014) - Xia, Yanwen; Liang, Yue; Li, Sen; Zhao, Junpu; Peng, Zhitao; Li, Hongguang; Liu, Hua; Sun, Zhihong; Zheng, Kuixing; Wei, Xiaofeng
Abstract: An energy measurement system in a Large-aperture high power laser experiment platform is introduced. The entire measurement system includes five calorimeters, which carry out the energy measurement of the fundamental frequency before the frequency conversion unit, remaining fundamental frequency, remain second-harmonics, third harmonics, as well as the energy balance measurement after the frequency conversion unit. Combinational indirect calibration and direct calibration are employed to calibrate the sampling coefficients of the calorimeters. The analysis of the data showed that, regarding the energy balance coefficients, combinational calibration approach gives a higher precision, and leads to an energy balance with 1%; and regarding the energy sampling coefficients for the various wavelengths after the frequency conversion, the results from direct and combinational calibration are consistent. The uncertainties for all energy sampling coefficients are within 3%, which guarantees the reliability of the energy measurement for the laser facility.